Revealing Impacts of Trees on Modeling Microclimate Behavior in Spaces between Buildings through Simulation Monitoring - Lirui Deng; Xibei Jia; Wei Wang; Syed Asad Hussain (Buildings, 2022)
Urban trees have been recognized as having different impacts on the microclimate and thermal comfort. Therefore, this study conducted on-site measurement and simulation to explore and clarify how trees impact the microclimate, thermal comfort, and façade temperature. A campus site was selected as the test field and two models—one with and one without trees—were built with the ENVI-met. Meanwhile, one microclimate station and four sensors were installed to simulate and validate the microclimate. Twelve blocks with different tree conditions were also selected to further investigate the specific impacts of trees. The results showed that, firstly, the transpiration and sheltering effect of trees that dominates on sunny days can decrease air temperature and the predicted mean vote. Secondly, trees’ effects on airflow, including on the wind channel and blocking effect, are dominant on cloudy days. Trees inside the group often exhibit the wind-blocking effect, while trees with a downwind determinant at the windward group edge usually exhibit the wind channel effect. Thirdly, high canopy coverage enhances trees’ sheltering effect on solar radiation. The study also provides design recommendations for campus building and trees that account for how trees help improve the microclimate, enhance comfort, and reduce energy consumption.